Blockchain Smart Contract Technology in Urban Energy Management System - Jin, Yueguang (Distributed Generation & Alternative Energy Journal, 2021)
Blockchain technology is considered a disruptive technology with real poten- tial for change after steam engines, electricity, and the internet. The regional electricity sales model based on blockchain technology will become an essential breakthrough in innovative city energy management. The thrust- less ingenious contract mechanism, the weakly centralized intelligent power energy micro-grid internal competitive energy business model, is based on blockchain technology. Its physical structure includes multiple levels such as the energy use layer, control layer, and functional layer. All transaction entities of the innovative power energy microgrid have an equal status in the blockchain system. The transaction energy includes cold, heat, electricity, gas, etc., and is distributed after bidding through energy routers and com- petitive trading platforms. This model uses multi-party bidding to optimize the allocation of resources such as cold, heat, and electricity, restores the commodity and financial attributes of energy and dramatically improves the energy efficiency and economic benefits of the power energy microgrid.